KOMUNIKASI MASSA DALAM PELAKSANAAN PROGRAM SIARAN RADIO (Analisis Tanggung Jawab Sosial Pelaksanaan Program Siaran Coffee Morning di Programa 2 LPP RRI Bengkulu) - Dete Konggoro; Dwi Kusuma Yuniarti; Maryaningsih - (UNIVED PRESS, Universitas Dehasen Bengkulu, 2015)
This study aimed to investigate the implementation of social responsibility in a broadcasting program Coffee Morning in programa 2 LPP RRI Bengkulu. This study used qualitative method, where the informants in this study was the Head of Press LPP RRI Bengkulu, Kasubsi Programa 2 LPP RRI, Stage Manager, Presenter, Presenter dialogue. Primary data in this study was obtained from interview to the informants, and secondary data obtained through library research. This study found that the implementation of social responsibility in a broadcasting program Coffee Morning in Programa 2 RRI Bengkulu LPP has been carried out based on the legal framework and institutions, meet the high standards of professionalism and information, correctness, accuracy, objectivity and balance, avoiding anything that might induce crime, detriment, public disorder or insult against ethnic or religious minorities, seeks to reflect the plurality and diversity of society, set high achievement standards, and intervention can be justified to safeguard the public interest. In other words, the implementation of this program fulfills a social responsibility towards the community listeners.